Epigenetic mechanisms in tumorigenesis, tumor cell heterogeneity and drug resistance - Wilting, Roel H.; Dannenberg, Jan-Hermen (Drug resistance updates, 2012)
Resistance of cancer cells to chemotherapeutics and emerging targeted drugs is a devastating problem in the treatment of cancer patients. Multiple mechanisms contribute to drug resistance such as increased drug efflux, altered drug metabolism, secondary mutations in drug targets, and activation of downstream or parallel signal transduction pathways. The rapid kinetics, the reversibility of acquired drug resistance and the absence of genetic mutations suggest an epigenetic basis for drug insensitivity. Similar to the cellular variance seen in the human body, epigenetic mechanisms, through reversible histone modifications and DNA methylation patterns, generate a variety of transcriptional states resulting in a dynamic heterogeneous tumor cell population. Consequently, epigenomes favoring survival in the presence of a drug by aberrant transcription of drug transporters, DNA-repair enzymes and pro-apoptotic factors render cytotoxic and targeted drugs ineffective and allow selection of rare drug-resistant tumor cells. Recent advances in charting cancer genomes indeed strongly indicate a role for epigenetic regulators in driving cancer, which may result in the acquisition of additional (epi)genetic modifications leading to drug resistance. These observations have important clinical consequences as they provide an opportunity for “epigenetic drugs” to change reversible drug-resistance-associated epigenomes to prevent or reverse non-responsiveness to anti-cancer drugs.